Container Yard Management Strategy to Support Operational Efficiency and Stacking Capacity - Sibuea, Rachel Maryam; Enrico, Muhammad Figo; Agustianty, Fortuna; Sinaga, Muhammad Risky; Cahya, Muhammad Gilar Ady (Journal of Collaborative Industrial Management (JCIM), 2025)
The efficiency of Container Yard (CY) operations plays a vital role in determining the overall performance of seaports. Batu Ampar Port in Batam, Indonesia, has experienced significant growth in container traffic over the past five years; however, operational efficiency has lagged due to limited infrastructure, suboptimal yard management, and minimal technology adoption. This study aims to analyze strategic CY management to improve operational efficiency by identifying current constraints and proposing integrated development strategies. Employing a qualitative descriptive approach within a feasibility study framework, data were collected through field observation, semi-structured interviews with key stakeholders, and document analysis. Findings reveal that Batu Ampar’s CY operates with a high yard utilization rate and extended dwell time, caused by outdated manual systems, inefficient container layout, and undertrained personnel. In contrast to global best practices, such as the Port of Singapore, Batu Ampar lacks essential systems like a Terminal Operating System (TOS) and real-time tracking via RFID or GPS. This research recommends adopting digital tools, conducting workforce training, restructuring the yard layout, and fostering public–private investment partnerships. These strategies are expected to reduce congestion, accelerate cargo flow, and enhance overall service reliability. The study contributes theoretically to port logistics literature by emphasizing the multidimensional integration of technology, human resources, and policy, while also offering practical guidance for modernizing medium-scale ports in developing regions.